Mineral and anti-nutrient contents of selected Sarawak local leafy vegetables - Saidin, Ainul Asyira; Saupi, Noorasmah; Sarbini, Shahrul Razid; Zakaria @ Ya, Muta Harah (Penerbit Universiti Malaysia Terengganu, 2016)
The use of wild plants as leafy vegetables have been developed over generations. Local people in Sarawak endowed with deep knowledge concerning the use of leafy vegetables collected from wild as food source and medicinal value. The leafy vegetables commonly consumed by local people namely Pycnarrhena tumectata (tubu), Smilax odoratissima (merudang) and Piper umbellatum offers good health benefits, yet the nutritional value is less documented especially on the anti-nutrient contents. P. tumectata used to add flavor and sweetness when cooking with meat dishes, the young shoots of S. odoratissima cooked or fried with anchovies and P. umbellatum commonly cooked or fried as dishes eat together with staple food. The samples were bought from Bintulu Tamu, Sarawak. The mineral content and anti-nutrient (oxalate and phytate) of the selected leafy vegetables were extracted using standard method of AOAC. All the vegetables contained higher concentration of K (501.20 ± 5.10 to 4006.00 ± 26.70 mg/100g) followed by Ca (215.20 ± 5.50 to 1925.50 ± 46.60 mg/100g), Mg (158.00 ± 5.20 to 732.50 ± 49.79 mg/100g) and P (154.40 ± 16.68 to 220.88 ± 19.82 mg/100g). Piper umbellatum showed significantly greatest concentration of Fe (48.64 ± 0.60 mg/100g), Zn (11.49 ± 0.79 mg/100g) and Mn (37.28 ± 3.03 mg/100g). The analysis on anti-nutrient content showed that the vegetables contain significantly low oxalate (10.00 ± 2.00 to 40.00 ± 1.60 mg/100g) but higher phytate (136.00 ± 67.00 to 412.00 ± 48.00 mg/100g). This information can provide basis for dietary planning for the nutritional required by the individuals that likely to consumed these leafy vegetables.